2009
DOI: 10.1590/s0100-69912009000400014
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Insulin resistance is a transitory phenomenon of the metabolic response to trauma. In uncomplicated operations it lasts for 2-4 weeks postoperatively, and is directly related to the magnitude of the injury. The fasting status caused by conventional fasting protocols aggravates this resistance and may induce hyperglycemia. Conventional preoperative fasting time may aggravate this resistance and increment the elevation of glycemia especially because it is frequently longer than the expected 6-8h and may reach 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Aguilar Nascimento et al . (2008) 13 compared the clinical outcomes before and after implementation of the ACERTO protocol and found mean a fasting time of 16 h in preoperative before to deploy of protocol 3 in 308 patients included in the survey. Cestonaro et al (2014) 8 found 16.5 h of mean fasting time to solids and 15.75 h to liquids in a university public hospital in the South of Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aguilar Nascimento et al . (2008) 13 compared the clinical outcomes before and after implementation of the ACERTO protocol and found mean a fasting time of 16 h in preoperative before to deploy of protocol 3 in 308 patients included in the survey. Cestonaro et al (2014) 8 found 16.5 h of mean fasting time to solids and 15.75 h to liquids in a university public hospital in the South of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Other care routine without scientific and safe evidences is related with digestive anastomoses, in which beliefs that bowel rest ensures adequate healing 12 , 18 . This practice could cause increased of inflammatory mediators, including insulin resistance, negative nitrogen balance, and this way, compromising the healing and increasing the risk of infections 2 , 3 , 7 , 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply of carbohydrates before surgery reduces the organic metabolic effects associated with surgical trauma. ( 19 , 29 , 30 ) It can be inferred that in greater magnitude surgeries, in which the organic response is more intense, this routine can promote a lower metabolic impact and therefore, provide important benefits to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged nightly fasting, instituted in order to prevent lung complications associated to vomiting and aspiration of gastric content may be harmful to the patient 4 . The organic answer to this procedure is aggravated with the operative trauma and the tissue damage that follows 3 .…”
Section: Introductionmentioning
confidence: 99%